2013
DOI: 10.1177/0009922813511146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pediatric Mental Health Screening on Clinical Discussion and Referral for Services

Abstract: Screening by parents improves detection of problems and fosters conversations with providers and subsequent connection with services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…A second example consisted of a study of pediatric mental health screening which found referrals to increase 2.4 times over baseline [54]. To explore plausible parameter values that might explain this result, we first calibrated the model to reflect the 10.3% referral rate reported at baseline in the study by changing the rate at which FN were lost to follow-up from 73 to 80%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second example consisted of a study of pediatric mental health screening which found referrals to increase 2.4 times over baseline [54]. To explore plausible parameter values that might explain this result, we first calibrated the model to reflect the 10.3% referral rate reported at baseline in the study by changing the rate at which FN were lost to follow-up from 73 to 80%.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one trial that resulted in a very large increase in both identification and referrals (falling well beyond the range predicted by our model) also was the only study in our sample to focus on suicide [53]—an outcome for which physicians are likely to regret FNs far more than for other behavioral conditions. A separate trial that reported a very large change in referrals also included provision of significant mental health services in addition to screening [54], which our model predicts will influence decision thresholds. Thus, the model offers plausible hypotheses to explain heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited to the studies from a variety of settings including hospital emergency departments [42,43,45,48,51], schools [47,50,57], community [28,29,53e55] (through social media, local radio, community organisation, research company), and hospital clinics, outpatient clinics, and mental health services [44,46,49,52,56]. The interventions subsequently took place in an emergency department [42,43,48,51], over the phone [28,47,50], letter [57], online [55], in the community (sports club or school hall) [29,53,54], over the phone and/or in person (hospital clinic or mental health service) [45,46], and in hospital clinics, outpatient clinics, or mental health services [44,49,52,56].…”
Section: Characteristics Of the Interventionsmentioning
confidence: 99%
“… Kazak and colleagues (2015) have published extensively on the use of the Psychosocial Assessment Tool (PAT 2.0), a screening tool based on this model, which has been used with a variety of pediatric populations including pediatric cancer, SCD, Congenital Heart Defects (CHD), diabetes, and organ transplant. There is emerging evidence that mental health screening in primary care settings may improve rates of referral to, and subsequent attendance at, psychiatric care appointments ( Jonovich & Alpert-Gillis, 2013 ). To our knowledge, there has not been any effort to translate this approach to neuropsychological service delivery.…”
Section: Public Health-based Models Of Assessment and Treatmentmentioning
confidence: 99%